High sensitivity fiber Bragg grating pressure sensor using thin metal diaphragm - Ahmad, H.; Wu, Yi Chong; Thambiratnam, K.; Zulklifi, M.Z.; Prabakaran, Poopalan, Prof. Madya; Thant, M. M. M; Harun, S. W. (Institute of Electrical and Elctronics Engineering (IEEE), 2010)
Link to publisher's homepage at http://ieeexplore.ieee.org/